Three job stress models and their relationship with musculoskeletal pain in blue- and white-collar workers - Herr, Raphael; Fischer, Joachim E.; Schmidt, Burkhard (Journal of psychosomatic research, 2015)
Musculoskeletal pain has been found to co-occur with psychosocial job stress. However, different conceptualizations of job stress exist, each emphasizing different aspects of the work environment, and it is unknown which of these aspects show the strongest associations with musculoskeletal pain. Further, these associations may differ for white-collar vs. blue-collar job types, but this has not been tested. The present study examined the independent and combined contributions of Effort-RewardImbalance (ERI), Job-Demand-Control (JDC) and Organizational Justice (OJ) to musculoskeletal pain symptoms among white- and blue-collar workers. Participants of a cross-sectional study (n=1634) completed validated questionnaires measuring ERI, JDC, and OJ, and reported the frequency of pain during the previous year at four anatomical locations (lower back, neck or shoulder, arms and hands, and knees/feet). Pain reports were summarized into a single musculoskeletal symptom score (MSS). Analyses were stratified for white- and blue-collar workers. Among white-collar workers, ERI and OJ were independently associated with MSS. In addition to these additive effects, significant 2-way and 3-way interactions indicated a synergistic effect of job stressors in relation to reported pain. In blue-collar workers, ERI and JDC independently associated with MSS, and a significant 3-way interaction was observed showing that the combination of job stressors exceeded an additive effect. ERI influences pain symptoms in both occupational groups. OJ was independent significant predictor only among white-collar workers, whereas JDC had additive predictive utility exclusively among blue-collar workers. Simultaneous exposure to multiple job stress factors appeared to synergize pain symptom reporting.